6-month survival of patients with acute myeloid leukemia who received modified chemotherapy at Wahidin Sudirohusodo Hospital - Edwinda D. Ratu; Tutik Hardjianti; Dimas Bayu; Syakib Bakri; Nasrum Mahmud; Andi Alfian Zainuddin (Romanian Medical Journal, 2024)
Background and aim. Standard chemotherapy for AML is daunorubicin combined with cytarabine. However, the combination chemotherapy also has side effects that are quite dangerous for AML patients. The purpose of this study is to assess the survival rates of AML patients treated at Wahidin Sudirohusodo Hospital in Makassar using modified chemotherapy regimens. Methods and material. This study was conducted at Wahidin Sudirohusodo Hospital in Makassar using a prospective cohort design. The study population included AML patients aged 18 years or older who had undergone modified chemotherapy for six months. Data on life expectancy, chemotherapy modifications, age, gender, and AML subtype were collected. Data were analyzed using SPSS version 22.0. Survival analysis was performed using the Kaplan-Meier curve, log-rank, and statistic test. Results. The cohort consisted of 25 males (51%) and 24 females (49%) with a mean age of 42 years. The 6-month survival rates were 68% for females and 50% for males. Age-based survival rates were 61.3% for patients <45 years, and 55.6 for those >45 years. Survival rates by AML subtype were 40% for M1, 63.3% for M2, 0% for M3, 60% for M4, and 66.7% for M5. The survival curve for the therapy regimen showed a significant relationship (p <0.05), with 86.7% survival for daunorubicin and 47.1% for cytarabine. Conclusions. Administration of daunorubicin and cytarabine chemotherapy is a variable that significantly determines the 6-month survival of AML patients.